The Investigations of Command Shaping and Non-collocated PID Schemes in Hybrid Trajectory and Sway Control of a DPTOC System - Mohd Ashraf, Ahmad (MedWell, Journal, 2010)

(untitled)
This paper presents investigations into the development of hybrid control schemes for trajectory tracking and sway control of a double-pendulum-type overhead crane (DPTOC) system. A nonlinear DPTOC system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. The proposed method, known as the Single Input Fuzzy Logic Controller (SIFLC), reduces the conventional two-input FLC (CFLC) to a single input single output (SISO) controller. The SIFLC is developed for position control of cart movement. This is then extended to incorporate input shaping and non-collocated parallel proportional-integral-derivative (PID) schemes for both hook and load sway angle suppression. The positive input shapers with the derivative effects are designed based on the properties of the system. The results of the response with the controllers are presented in time and frequency domains. The performances of control schemes are examined in terms of level of input tracking capability, sway angle reduction and time response specifications in comparison to SIFLC controller. Finally, a comparative assessment of the control techniques is discussed and presented.